A new insight into the impact of different proteases on SILAC quantitative proteome of the mouse liver. Issue 15 (20th June 2013) - Ma, Jie; Li, Wenbo; Lv, Yongzhuang; Chang, Cheng; Wu, Songfeng; Song, Lei; Ding, Chen; Wei, Handong; He, Fuchu; Jiang, Ying; Zhu, Yunping
<x xml:space="preserve">Abstract</x> In this study, we examined the use of multiple proteases (trypsin, LysC, tandem LysC/trypsin) on both protein identification and quantification in the Lys‐labeled SILAC mouse liver. Our results show that trypsin and tandem LysC/trypsin digestion are superior to LysC in peptides and protein identification while LysC shows advantages in quantification of Lys‐labeled proteins. Combination of experimental results from different proteases (LysC and trypsin) enabled a significant increase in the number of identified protein and protein can be quantified. Thus, taking advantage of the complementation of different protease should be a good strategy to improve both qualitative and quantitative proteomics research.